Lead Leakage Preventable Fullerene‐Porphyrin Dyad for Efficient and Stable Perovskite Solar Cells. (18th December 2021) - Liang, Yuming; Song, Peiquan; Tian, Hanrui; Tian, Chengbo; Tian, Wanjia; Nan, Ziang; Cai, Yuanting; Yang, Panpan; Sun, Chao; Chen, Jingfu; Xie, Liqiang; Zhang, Qianyan; et al.
Abstract: Designing functional fullerenes with roles beyond defect passivation and electron‐transporting for perovskite solar cells (PSCs) is essential to the development of fullerenes and PSCs. Here, the authors design and synthesize a functional fullerene, FPD, composed of a C60 cage, a porphyrin ring, and three pentafluorophenyl groups. The structure features of FPD enable it can form chemical interactions with the perovskite lattices. These interactions enhance the defect passivation effect and prevent the decomposition of perovskite under irradiation. As a result, the FPD‐based device yields an improved power conversion efficiency of 23% with substantially enhanced operational stability ( T 80 > 1500 h). Furthermore, once got damaged, the FPD can prevent lead leakage by forming a stable and water‐insoluble complex (FPD‐Pb). Their findings provide a novel strategy to achieve high‐performance and eco‐friendly PSCs with functional fullerene materials. Abstract : The authors demonstrate that designing functional fullerenes with roles beyond defect passivation is essential for perovskite solar cells (PSCs). By taking the advantages of fullerene, porphyrin, and pentafluorophenyl, a novel fullerene‐porphyrin dyad is intentionally synthesized to stitch grain boundaries and trap lead ions in the perovskite film by forming chemical interactions in‐situ. This robust strategy yields high‐performance and eco‐friendly PSCs.